2008
DOI: 10.1111/j.1439-0272.2007.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm ultrastructure and meiotic segregation in a group of patients with chronic hepatitis B and C

Abstract: Little is known about the effect of chronic hepatitis B and hepatitis C on sperm quality. In this study we analysed sperm quality from selected patients with chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infections. Semen samples were examined by light and transmission electron microscopy (TEM). TEM data were elaborated with a mathematical formula able to indicate a fertility index and the presence of the three main sperm pathologies: apoptosis, immaturity and necrosis. Meiotic chromosome segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
2
18
0
2
Order By: Relevance
“…6 Thus, HBV infection can induce chromosome aberrations, leading to hereditary defects in male germinal cells and problems in spermatogenesis. Consistent with this idea, Moretti et al 9 had observed that HBV infection increased the percentage of phenotypic sperm pathologies, such as necrosis, apoptosis and immaturity. In addition, a recent in vitro study on HBV S protein and sperm function demonstrated that sperm treated with S protein exhibited lower fertilisation rate and index due to reduced sperm motility from mitochondrial injury.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…6 Thus, HBV infection can induce chromosome aberrations, leading to hereditary defects in male germinal cells and problems in spermatogenesis. Consistent with this idea, Moretti et al 9 had observed that HBV infection increased the percentage of phenotypic sperm pathologies, such as necrosis, apoptosis and immaturity. In addition, a recent in vitro study on HBV S protein and sperm function demonstrated that sperm treated with S protein exhibited lower fertilisation rate and index due to reduced sperm motility from mitochondrial injury.…”
Section: Discussionsupporting
confidence: 58%
“…One possible explanation for this difference is that sperm infected with HBV could have also been injected into the oocyte during ICSI. This is unlikely though because HBV-infected sperm generally have a lower probability of successful fertilisation by either IVF or natural conception, 9 as sperm infected with HBV S protein was shown to have decreased fertilising ability. 17 Moreover, HBV DNA could be detected in the semen of HBV-infected patients, 5 and even after thoroughly washing sperm to reduce the risk of viral transmission, about 10% remained HBVpositive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor semen parameters had been found in HBV-infected men (Vicari et al, 2006;Lee et al, 2010;Lorusso et al, 2010;Zhou et al, 2011). Also, HBV infection is associated with sperm apoptosis and necrosis resulted out of normal range (Moretti et al, 2008). Furthermore, HBV infection could induce sperm chromosome aberrations and cause serious damage on sperm genetic material (DNA) and mitochondrial membrane potential (Huang et al, 2003;Zhou et al, 2009;Chen et al, 2011).…”
Section: Hepatitis B Virus (Hbv) Infection Is a Major Health Problem mentioning
confidence: 99%